2010
DOI: 10.1038/bmt.2010.106
|View full text |Cite
|
Sign up to set email alerts
|

Low risk of symptomatic venous thromboembolic events during growth factor administration for PBSC mobilization

Abstract: The use of erythropoietic agents has been associated with an increased risk of venous thromboembolic events (VTEs), especially in patients with underlying malignancies. However, it is not known whether there is an increased risk of VTE associated with granulocyte growth factors. We reviewed 621 patients undergoing PBSC mobilization using granulocyte growth factors, alone or in combination with CY. Patients with a diagnosis of AL amyloidosis (AL: 114; 18%), multiple myeloma (MM: 278; 44%) Hodgkin lymphoma (HL: … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
6
0
1

Year Published

2012
2012
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(7 citation statements)
references
References 12 publications
0
6
0
1
Order By: Relevance
“…In contrast to the DLBCL group, patients treated with HL receiving ABVD chemotherapy have an overall low neutropenia risk. Although some patients required G‐CSF administrations, the data from healthy donors and stem cell mobilizations indicated that the use of G‐CSF is not associated with an increased risk of thrombotic events . Furthermore, along with the treatment time and achievement of disease control, the risk of developing VTE decreases.…”
Section: Discussionmentioning
confidence: 99%
“…In contrast to the DLBCL group, patients treated with HL receiving ABVD chemotherapy have an overall low neutropenia risk. Although some patients required G‐CSF administrations, the data from healthy donors and stem cell mobilizations indicated that the use of G‐CSF is not associated with an increased risk of thrombotic events . Furthermore, along with the treatment time and achievement of disease control, the risk of developing VTE decreases.…”
Section: Discussionmentioning
confidence: 99%
“…95,96 Early observations indicated that the powerful mobilizing cytokine G-CSF might, in fact, induce a hypercoagulant state in healthy donors, as evidenced by increased thrombin generation, and consequently carry a risk of thrombosis. 97,98 The expression of the major thrombin receptor PAR1 assessed by microarrays was found to be 3.3-fold higher in G-CSFmobilized human CD34 + stem and progenitor cells compared with steady-state BM CD34 + HSPCs. 99 These observations paved the way for the hypothesis that stress-induced, accelerated thrombin generation may promote PAR1 + HSPC exit from the BM, and that the higher PAR1 surface expression by the mobilized human CD34 + stem and progenitor cells has motility-supporting functions.…”
Section: Thrombin/par1 Signaling Regulates Hsc Mobilizationmentioning
confidence: 99%
“…95,96 Early observations indicated that the powerful mobilizing cytokine G-CSF might in fact induce a hypercoagulant state in healthy donors, as evidenced by increased thrombin generation, and consequently carry a risk of thrombosis. 97,98 . The expression of the major thrombin receptor PAR1 assessed by microarrays was found to be 3.3-fold higher in G-CSF–mobilized human CD34 + stem and progenitor cells compared with steady-state BM CD34 + HSPCs.…”
Section: Thrombin/par1 Signaling Regulates Hsc Mobilizationmentioning
confidence: 99%
“…77 G-CSF is a potent cytokine that is used to clinically induce neutrophil maturation and mobilization of dormant HSCs into the circulation. 78 G-CSF injection leads to a transient procoagulant state 77,79,80 that may contribute to HSC mobilization, because, similar to thrombin injection, 56 G-CSF also decreases BM CXCL12 levels and upregulates CXCR4 on HSCs. 81 PAR1 is essential for CXCL12-mediated HSPC migration and chemotaxis, 56 and G-CSF-mobilized human CD34 1 HSPCs have elevated PAR1 levels compared with steady-state BM HSPCs.…”
Section: Coagulation and Fibrinolysis In The Response To Bm Stressmentioning
confidence: 99%